2004
DOI: 10.1042/bj20040158
|View full text |Cite|
|
Sign up to set email alerts
|

Cell detachment and apoptosis induction of immortalized human prostate epithelial cells are associated with early accumulation of a 45 kDa nuclear isoform of clusterin

Abstract: Clusterin, ubiquitously distributed in mammalians, was cloned and identified as the most potently induced gene during rat prostate involution following androgen deprivation. Also found to be involved in many other patho-physiological processes, its biological significance is still controversial, particularly with regard to apoptosis. We previously showed that transient over-expression of clusterin blocked cell cycle progression of simian-virus-40-immortalized human prostate epithelial cell lines PNT1A and PNT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 54 publications
6
56
0
1
Order By: Relevance
“…In contrast, Trougakos et al (16,29) reported that in osteosarcoma cells either clu overexpression or clu knockdown could result in apoptosis of these cells. Furthermore, it recently became evident that numbers of clu functions were related to intracellular forms of the protein, in particular for apoptosis (30). Lastly, it has been demonstrated that overexpression of intracellular CLU caused clonogenic toxicity in PC-3 androgen-independent prostate cancer cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Trougakos et al (16,29) reported that in osteosarcoma cells either clu overexpression or clu knockdown could result in apoptosis of these cells. Furthermore, it recently became evident that numbers of clu functions were related to intracellular forms of the protein, in particular for apoptosis (30). Lastly, it has been demonstrated that overexpression of intracellular CLU caused clonogenic toxicity in PC-3 androgen-independent prostate cancer cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides and small interfering RNAs (siRNA) targeting the full-length CLU have been reported to induce apoptosis and chemosensitivity in vitro in prostate cancer xenografts (26)(27)(28)(29) and in prostate cancer patients (30,31). On the other hand, nCLU accumulation has been observed in dying prostate cells challenged with proapoptotic stimuli (4,5,17). Overexpression of nCLU has been reported to induce G 2 -M phase arrest and caspase-dependent apoptosis in prostate cancer cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…CLU is considered an enigmatic protein because of the difficulties in the definition of its precise functions; at the moment, an important debate concerns its implication in carcinogenesis, particularly in prostate cancer development. On this issue, the data currently available are controversial because CLU has been suggested as being either a proapoptotic or a prosurvival factor (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Such observations were consistent with the reports that accumulation of an intracellular nCLU isoform is associated with anoikis induction in PNT1A cells. 25 Transient nCLU overexpression triggered cell death in SKOV3 cells…”
Section: Subcellular Localization Of Clu Isforms In Skov3 Cells and Tmentioning
confidence: 99%